2015
DOI: 10.5812/jjm.22935
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and Types of Multidrug-Resistant Acinetobacter baumannii in Different Departments of a General Hospital

Abstract: Background:Acinetobacter baumannii is the most prevalent strain in hospitals and different clinical departments.Objectives:The current study aimed to investigate the genetic characteristics and resistance mechanisms of A. baumannii isolated from clinical samples in Shaoxing people’s hospital affiliated to Zhejiang University, Shaoxing, China.Patients and Methods:Acinetobacter baumannii strains were isolated from blood, phlegm and skin of the patients hospitalized in different departments as respiratory medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…A study conducted in Pakistan also found that the ST2 clone-harboring bla NDM-1 and bla OXA-23 , which are widely distributed in ICUs, could prompt increased mortality ( Ejaz et al, 2021 ). Notably, a study in another Chinese hospital in Shanghai reported the presence of bla OXA-23 in all CRAB strains ( Wang et al, 2021 ), and it was found that the predominant clone of CRAB was ST208, which was consistent with the results obtained by Qian et al (2015) .…”
Section: Drug Resistance Mechanism and Homology Of Crab Isolated From...supporting
confidence: 82%
“…A study conducted in Pakistan also found that the ST2 clone-harboring bla NDM-1 and bla OXA-23 , which are widely distributed in ICUs, could prompt increased mortality ( Ejaz et al, 2021 ). Notably, a study in another Chinese hospital in Shanghai reported the presence of bla OXA-23 in all CRAB strains ( Wang et al, 2021 ), and it was found that the predominant clone of CRAB was ST208, which was consistent with the results obtained by Qian et al (2015) .…”
Section: Drug Resistance Mechanism and Homology Of Crab Isolated From...supporting
confidence: 82%
“…15 Moreover, at the same hospital but in different wards, the distribution of clones and mechanism of resistance also varied in different clinical departments. 16 Thus, our study, performed in a private hospital, revealed the same bla OXA23 as related studies but reported two patients carrying two carbapenemase genes (bla OXA23 and bla NDM1 ) simultaneously.…”
Section: Discussionsupporting
confidence: 76%
“…19 In the present study, 80 A. baumannii isolates were collected from the diagnostic laboratory of a burn hospital which is very high considering the duration of the research period (two months) compared to similar studies in other hospitals. 20,21 Since this level of infection was found in hospitals during a two-month period, further investigation is needed to determine whether there is a problem with cross-transmission, either within the hospital in question and/or other hospitals from which patients are received into this hospital. Our hospital is the major burn center and many burn patients from other hospitals are hospitalised in the ICU of the targeted hospital; in addition, many clinical samples are transferred from other hospitals to this one for the culturing and confirmation of bacterial identification.…”
Section: Discussionmentioning
confidence: 99%